“Creación de una microempresa de pastelería, confitería y bocaditos con inclusión de mano de obra de madres de niños y jóvenes con capacidades diferentes en el Sur de la Cuidad de Quito, Provincia de Pichincha” - Suntasig Suntaxi, Evelyn Rosario (2010)
This thesis aims at creating a micro-bakery, confectionery and snacks including mothers of children and youth with disabilities in southern Quito, Pichincha province, a project that is funded by the state through the Ministry of Economic and Social Inclusion (MIES) and the Institute of Popular and Solidarity Economy (IEPS).